High-accuracy absolute magnetometry with application to the Fermilab Muon g-2 experiment. (22nd December 2021) - Flay, D.; Kawall, D.; Chupp, T.; Corrodi, S.; Farooq, M.; Fertl, M.; George, J.; Grange, J.; Hong, R.; Osofsky, R.; Ramachandran, S.; Swanson, E.; et al.
Abstract: We present details of a high-accuracy absolute scalar magnetometer based on pulsed proton NMR. The B-field magnitude is determined from the precession frequency of proton spins in a cylindrical sample of water after accounting for field perturbations from probe materials, sample shape, and other corrections. Features of the design, testing procedures, and corrections necessary for qualification as an absolute scalar magnetometer are described. The device was tested at B = 1.45 T but can be modified for a range exceeding 1–3 T. The magnetometer was used to calibrate other NMR magnetometers and measure absolute magnetic field magnitudes to an accuracy of 19 parts per billion as part of a measurement of the muon magnetic moment anomaly at Fermilab.